Studi Kriminologi Dalam Penanggulangan Tindak Pidana Narkotika - Peter Guntara; Fayza Galih Nur Rohmah; Mahageng Kusumaningtyas; M Susilo Agung Saputro (Sanskara Hukum dan HAM, 2026)
Drug abuse in Indonesia is a complex form of crime influenced by structural, social, and psychological factors. This article analyzes the role of criminological theory in formulating strategies to combat drug crimes based on a literature review and empirical findings in the Case Study of Drug Abuse in Kolaka Regency, which shows a dominant pattern of methamphetamine use triggered by social interactions and weak social control. The theory of association differentiation explains that behavior is learned through social interaction, while the theory of social control emphasizes that deviance increases when social ties weaken. Labeling theory provides an understanding of stigma that increases recidivism, making a rehabilitative approach more effective than a punitive one. The implementation of criminological theory is seen in the establishment of Desa Bersinar by the Kolaka National Narcotics Agency (BNNK) as a preventive measure, as well as surveillance, undercover buying, and controlled delivery techniques by the Narcotics Unit as repressive measures. The results of the study show that the integration of criminological theory into countermeasure policies through prevention, rehabilitation, and proportional law enforcement is more effective than a purely repressive approach, and confirms that criminological theory plays a role as a practical instrument in formulating strategies for countering narcotics crimes in Indonesia.